Optimal planning of hybrid electric-hydrogen energy storage systems via multi-objective particle swarm optimization - Xuan, Juqin; Chen, Zhuolin; Zheng, Jieyun; Zhang, Zhanghuang; Shi, Ying (Frontiers in Energy Research, 2023)
In recent years, hydrogen is rapidly developing because it is environmentally friendly and sustainable. In this case, hydrogen energy storage systems (HESSs) can be widely used in the distribution network. The application of hybrid electric-hydrogen energy storage systems can solve the adverse effects caused by renewable energy access to the distribution network. In order to ensure the rationality and effectiveness of energy storage systems (ESSs) configuration, economic indicators of battery energy storage systems (BESSs) and HESSs, power loss, and voltage fluctuation are chosen as the fitness function in this paper. Meanwhile, multi-objective particle swarm optimization (MOPSO) is used to solve Pareto non-dominated set of ESSs' optimal configuration scheme, in which the technique for order preference by similarity to ideal solution (TOPSIS) based on information entropy weight (IEW) is used select the optimal solution in Pareto non-dominated solution set. Based on the extended IEEE-33 system and IEEE-69 system, the rationality of ESSs configuration scheme under 20 % and 35 % renewable energy penetration rate is analyzed. The simulation results show that ESSs configuration scheme obtained by MOPSO can improve the voltage quality of the distribution network with renewable energy access, reduce the voltage fluctuation of the distribution network, improve the stability of the power system, and improve the power quality of users.